If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+27=11x+53
We move all terms to the left:
3x+27-(11x+53)=0
We get rid of parentheses
3x-11x-53+27=0
We add all the numbers together, and all the variables
-8x-26=0
We move all terms containing x to the left, all other terms to the right
-8x=26
x=26/-8
x=-3+1/4
| 16x-36=7x-8 | | 5(2+x)=11 | | 6(7-4x)+7(2-5x)=45 | | 10x2-7x-5=0 | | -5m+8=33 | | 5505=2x+2000 | | -30=-2+7x | | 15x−14x−x+4x=4 | | -6m+8=-46 | | 3(0)+2y=3 | | -6p-4(4-3p)=3(p-4)-19 | | 25.8=1/4x | | 7x/2+5=3x/5-4 | | 3c÷9=4-c | | X^2+22x-5040=0 | | X+1/4x=4.5 | | 4(2x+13|)=80 | | 42=15u-9u | | 5x²-2x-3=0 | | 8+3(x+8)=-2x+9(x+8) | | 4x+-1=3x+3 | | .25(x)=750 | | 18x=-11x | | 5x-3+21-x=0 | | 6d-3=4d+17 | | 8x^2+10x-102=0 | | X^2+45+14x=0 | | 13.x+6=0 | | 2.7=k-8.5 | | (6x-1)(2x+1)10-(2x+1)(x)5=(6x-1)(x)15 | | 42=3(5x-10 | | -(v-1)=-6v+26 |